2020
DOI: 10.3892/etm.2020.9433
|View full text |Cite
|
Sign up to set email alerts
|

PM2.5 induces autophagy‑mediated cell apoptosis via PI3K/AKT/mTOR signaling pathway in mice bronchial epithelium cells

Abstract: Air pollution can highly impact the respiratory system in healthy individuals. Studies have indicated that particles with an aerodynamic diameter of ≤2.5 µm (PM2.5) can be considered to be harmful for lung alveoli and bronchial epithelium cells. PM2.5 can be directly inhaled and can deeply penetrate into the lung alveoli, causing lung dysfunction. However, the toxicological mechanism mediated by PM2.5 for respiratory disease has still not been clearly determined. The purpose of the current study was to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 35 publications
1
37
0
1
Order By: Relevance
“…The IL-6 receptor antagonist tocilizumab has been used in some cases of severe COVID-19 [ 86 , 87 , 88 , 89 , 90 ]. However, the benefits of tocilizumab for the treatment of COVID-19 are uncertain, [ 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ] and the Italian Medicines Agency (AIFA) announced on June 18, 2020 that tocilizumab (Actemra) did not improve COVID-19 outcomes [ 91 , 92 , 93 ]. However, a recent meta-analysis reported a reduced mortality prevalence in patients treated with tocilizumab [ 97 ].…”
Section: Diabesity Meta-inflammation and Il-6: The Role In Severmentioning
confidence: 99%
“…The IL-6 receptor antagonist tocilizumab has been used in some cases of severe COVID-19 [ 86 , 87 , 88 , 89 , 90 ]. However, the benefits of tocilizumab for the treatment of COVID-19 are uncertain, [ 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ] and the Italian Medicines Agency (AIFA) announced on June 18, 2020 that tocilizumab (Actemra) did not improve COVID-19 outcomes [ 91 , 92 , 93 ]. However, a recent meta-analysis reported a reduced mortality prevalence in patients treated with tocilizumab [ 97 ].…”
Section: Diabesity Meta-inflammation and Il-6: The Role In Severmentioning
confidence: 99%
“…Therefore, blocking of the mTOR pathway promotes longevity but might also cause impairment of energy metabolism and induce long-term health consequences [ 124 ]. In mice, PM 2.5 exposure causes overexpression of mTOR, leading to apoptosis [ 125 ], as well as pulmonary inflammation and fibrosis [ 126 ].…”
Section: Oxidative Stress and Inflammation By Air Pollutionmentioning
confidence: 99%
“…Women with MS in the postpartum period are even more vulnerable to relapses and infections. Another case report of SARS-CoV-2 infection in a 40-year-old woman with recurrent RRMS demonstrated that the relapse of MS began right after SARS-CoV-2 infection [ 127 ]. Five weeks postpartum, the patient complained of paresthesia and disability in the right limbs, with the onset two weeks before.…”
Section: Does Infection Of Sars-cov-2 May Be An Actual Neurodegenementioning
confidence: 99%
“…She was discharged after two consecutive negative PCRs. After two weeks, PCR, IgG, and IgM for SARS-CoV-2 were negative, along with the remission of the neurological deficit [ 127 ].…”
Section: Does Infection Of Sars-cov-2 May Be An Actual Neurodegenementioning
confidence: 99%